Komponen TPACK yang Tepat untuk Mengatasi Kesalahpahaman pada Uji Inventarisasi Konsep Gaya - A Halim; Meisy Adha Rizki; Hafnati Rahmatan; Muhammad Syukri; Agus Wahyuni; Yusrizal Yusrizal (Postgraduate, University of Mataram, 2024)
Misconception is one of the obstacles in the achievement of physics learning and must be immediately corrected so that there is no retention of misconceptions in subsequent knowledge. One way to prevent and reduce misconceptions that occur is with the teachers skill of Technological Pedagogical and Content Knowledge (TPACK). Teachers who integrate TPACK in learning can prevent misconceptions and find solutions to overcome the misconceptions. This study aims to determine the TPACK skill of teachers in overcoming misconceptions and the appropriate TPACK components to reduce misconceptions based on concepts on the three tier test of FCI (Force Concept Inventory). The research method used is mixed method with concurrent embedded design. The main data in this study is TPACK which is qualitative data and supporting data is students misconception which is quantitative data. The results showed a decrease in misconceptions after being given an understanding of the concept using the teacher's TPACK skill. The components used during the teacher's reduction of misconceptions based on the concepts in the FCI three tier test of FCI Â are TPACK and PCK components. So it can be concluded that the teacher's TPACK skill can reduce the misconceptions that occur in the three tier test of FCI